2-chloroadenosine attenuates kainic acid-induced toxicity within the rat straitum: relationship to release of glutamate and Ca2+ influx. - Arvin, B. (1989)
1. The mechanism by which 2-chloroadenosine (2-chloroado) exerts a neuroprotective action against the excitotoxic effect of kainic acid (KA) when injected into the rat striatum was investigated. 2. Histological examination two weeks after a single injection of KA (2.2 nmol) into rat striatum revealed widespread neuronal damage. Co-injection of 2-chloroado (6-25 nmol) with the neurotoxin afforded dose-dependent neuroprotection. This effect was reversed by administration of an equimolar concentration of the adenosine receptor antagonist theophylline. 3. Both K+ (30 mM) and KA (1 mM) enhanced the release of endogenous glutamate from guinea-pig purified cerebrocortical synaptosomes in a predominantly (approximately 70%) Ca2+-dependent manner. 2-Chloroado (10 nM-1 microM) inhibited the release of glutamate evoked by both KA and K+. These effects were partially reversed by the selective A1-adenosine receptor antagonist 8-cyclopentyltheophylline (CPT) (1 microM). 4. Crude rat cortical synaptosomes were loaded with the fluorescent calcium indicator quin-2 and Ca2+ influx monitored following two successive depolarising stimuli (30 mM K+; 'S1' and 'S2'). 2-Chloroado (10 nM-1 microM) produced a dose-dependent reduction in the S2:S1 ratio when added before the S2 period of stimulation. This effect was reversed by 1 microM theophylline. However, KA (1 mM) failed to enhance Ca2+ influx in the same preparation. 5. These results suggest that the anti-excitotoxic action of 2-chloroado is mediated primarily through a specific presynaptic receptor mechanism involving reduction of transmitter glutamate release, possibly occurring through an inhibition of Ca2+ influx.